1999
DOI: 10.1002/(sici)1099-1085(19990228)13:3<277::aid-hyp738>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ground water on surface water conditions in a glacial flood plain of the Swiss Alps

Abstract: Abstract:Hydrological exchange processes in alluvial¯ood plains occur along several major pathways operating at dierent scales. Ground water±surface water interactions exert major control on structural and functional attributes of stream ecosystems. The role of ground water on environmental conditions in surface water habitats was investigated as part of a holistic ecological study of Val Roseg, a complex glacial¯ood plain in the Swiss Alps. Six channel types were identi®ed based on surface hydrological connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 36 publications
(33 reference statements)
8
81
0
Order By: Relevance
“…These habitats may act as sources of new colonisers rather than as potential refugia for inhabitants of main channel braids during floods (Ward et al 1999a).…”
Section: 1 M a I N C H A N N E L I N V E R T E B R A T E C O M M U mentioning
confidence: 99%
“…These habitats may act as sources of new colonisers rather than as potential refugia for inhabitants of main channel braids during floods (Ward et al 1999a).…”
Section: 1 M a I N C H A N N E L I N V E R T E B R A T E C O M M U mentioning
confidence: 99%
“…River-floodplain ecosystems are expanding, contracting, and often fragmented ecosystems (Stanley et al, 1997;Ward et al, 1999c;Malard et al, 1999;Tockner et al, 2000). These changes in size are thought to control habitat availability and environmental conditions as well as faunal/floral composition and ecological processes.…”
Section: A B Perspectivesmentioning
confidence: 99%
“…Researchers have reported that hyporheic discharge both cools and/or warms stream channel water [e.g., Ward et al, 1999;Cozzetto et al, 2006;Fernald et al, 2006]. Similarly, hyporheic water temperature may decrease with depth [e.g., Evans and Petts, 1997;Schmidt et al, 2006] or increase with depth [e.g., Hanrahan, 2007].…”
Section: Introductionmentioning
confidence: 99%